EKSISTENSI KAJIAN TAUHID DALAM KEILMUAN USHULUDDIN - Saidul Amin (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The study of Tawheed in Islam is the regional foundation for discussion of aqeedah.in this case aqeedah is something very important and fundamental in the formation of good character in the life of a Muslim, which is used as a pillar and foundation of religion, so as to be able to motivate a person in the form of trust and faith. therefore, aqeedah as the foundation for establishing Islamic buildings is the beginning of noble character. If someone has strong Aqeedah, surely they will carry out their worship in an orderly, noble manner, and bermu'amalat well. all the worship that we carry out if without the foundation of Aqeedah then the worship will not be accepted.